Contact interaction of two rectangular plates made from different materials with an account of physical nonlinearity; Nonlinear Dynamics; Vol. 91, iss. 2 - Awrejcewicz J.; Krysko V. A.; Zhigalov M. V. Maksim; Krysko A. V. Anton Vadimovich (2018, 2018)
Title screen